Proceedings of the First Indonesian Communication Forum of Teacher Training and Education Faculty Leaders International Confere 2018
DOI: 10.2991/ice-17.2018.85
|View full text |Cite
|
Sign up to set email alerts
|

Moral Cognitive Development of Primary School Students in Thematic Integrated Curriculum

Abstract: This study aims to determine the moral cognitive development of elementary school students through learning based on cognitive models of morals in the integrated thematic curriculum (BKMT). The research method used is the quasi experiment with the one group pretest-post-test design. The sample of this research is students of class V SD Ketabang Surabaya which amounts to 37 people. The instrument used to collect the data in the study was the Moral Reasoning Test compiled by Kohlberg with modifications. The data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
2
0
3
Order By: Relevance
“…Perkembangan moral kognitif siswa SD bisa ditingkatkan dengan penggunaan modelmodel pembelajaran yang mengedepankan pendidikan moral. Hal ini penting karena model pembelajaran moral yang menekankan aspek kognitif, merupakan upaya kongkrit agar siswa dapat melampaui tahap perkembangan moral kognitif yang telah dicapai (Satianingsih, Maftuh, & Syaodih, 2017). Selanjutnya dapat digunakan oleh siswa untuk mencapai tahap yang lebih tinggi.…”
unclassified
See 1 more Smart Citation
“…Perkembangan moral kognitif siswa SD bisa ditingkatkan dengan penggunaan modelmodel pembelajaran yang mengedepankan pendidikan moral. Hal ini penting karena model pembelajaran moral yang menekankan aspek kognitif, merupakan upaya kongkrit agar siswa dapat melampaui tahap perkembangan moral kognitif yang telah dicapai (Satianingsih, Maftuh, & Syaodih, 2017). Selanjutnya dapat digunakan oleh siswa untuk mencapai tahap yang lebih tinggi.…”
unclassified
“…Penelitian Satianingsih et al (2017) dengan judul "Moral Cognitive Development of Primary School Students in Thematic Integrated Curriculum". Dalam penelitian ini dikatakan bahwa perkembangan moral kognitif siswa Sekolah Dasar sangat berkembang melalui kurikulum tematik terintegrasi.…”
unclassified
“…Melalui model pembelajaran kognitif moral yang di prakarsai oleh Kohlberg (Kohlberg, 1976) dengan sintaksnya menyajikan dilema moral untuk meningkatkan kematangan pertimbangan moral, model pendidikan moral ini banyak dikembangkan juga dengan pengembangan dari berbagai aspek. Misalnya penelitian Sarbaini (Sarbaini, 2012) mengenai diskusi dilema moral di SMP, Setianingsih (Satianingsih., Maftuh, & Syaodih, 2018) cerita dilema moral pada tematik di Sekolah Dasar (Wismaliya et al, 2019) cerita dilema moral berbasis kearifan lokal masyarakat sunda dan (Hakam, Fitriya, & Wismaliya, 2020) cerita dilema moral pada pembelajaran olahraga.…”
Section: A Pendahuluanunclassified
“…This is a good habit that impacts the character of social care that is increasingly attached. In the opinion of Satianingsih et al (2022), a sense of social care at school can be shown by helping each other, greeting each other, and mutual respect among school members. Having a soul of social concern is very important because we cannot live alone.…”
Section: Respect the School Communitymentioning
confidence: 99%